Rare earth elements determination and distribution patterns in granite rock samples by using INAA absolute method - I. A., Alnour; M. S., Eli; H., Wagiran; N., Ibrahim; S., Hamzah; B. S., Wee (Springer, 2015)
This work determined elemental concentrationsfor rare earth elements (REE) in granite rock samples usingthe INAA absolute method. The accuracy of INAA abso-lute method was determined by analyzing two of USGSSTM-1 and MAG-1 standards. The analytical resultsagreed reasonably well with certified values. In general, allanalytical results hadZscore less than 1.0 excepting Yb.The REE found in granite rock samples ranged from 116 to325 mg kg-1. The total content of REE in granite rocksamples was 206 mg kg-1. Patterns for REE were alsostudied in the present work.